A Boas-type theorem for α-monotone functions - Dyachenko, M.; Mukanov, A.; Nursultanov, E. (MATHEMATICA SCANDINAVICA, 2017)
We define the class of α-monotone functions using fractional integrals. For such functions we prove a Boas-type result on the summability of the Fourier coefficients.